Manajemen Holistik dengan Pendekatan Kedokteran Keluarga pada Pasien Wanita 37 Tahun dengan Hipertensi Primer - Annisa Putri Perdani; Khairun Nisa Berawi (Penerbit Goodwood, 2021)
Purpose: This study aimed to identify risk factors, clinical problems and provide management of patients with the implementation of holistic family physician services based on evidence-based medicine approach to patient and family-centered approach. Research methodology: This study is a case report. Primary data were obtained through history taking (directly from the patient and indirectly from family members), physical examination, and a home visit to complete the family, psychosocial and environmental data. Secondary data were obtained from the medical records of the patient at the health center. The assessment was based on a holistic diagnosis from the beginning, process, and the end of quantitative and qualitative studies. Results: A 37-year-old female was diagnosed with primary hypertension with worries that his disease would get worsen into a stroke. Patients do not know exactly what diet is recommended for hypertensive patients. The evaluation results obtained that complaints and worries of patients were reduced, the knowledge of patients and their families regarding hypertension increased and behavior related to hypertension improved. Contribution: Holistic management has been done with the approach of a family doctor, Mrs. S age 37 years with primary hypertension adjusted for EBM based on baseline holistic diagnostics. These interventions have increased the patient's knowledge and changed some of the patient's behavior and his family, as indicated by improvements in the final holistic diagnostics.